Keteladanan Guru Dalam Membentuk Karakter Siswa: (Studi Kasus di SMP Negeri 35 Medan) - Dewi Romantika Tinambunan; Dules Ery Pratama; Jahya Adiputra Simbolon; Manotar Sinaga; Muhammad Ansar; Ruth Yessika Siahaan; Jamaludin Jamaludin (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Teachers as educators have a very important role in shaping students' character through the example shown by the teacher. The teacher's caution in acting and speaking is something that must be paid attention to so as not to set the wrong example to students. The aim of this research is to examine how teacher example shapes the character of students at SMP Negeri 35 Medan. The method in this research is to use a qualitative method with a descriptive approach. Data collection techniques use direct observation and interviews.